THE RELATIONSHIP BETWEEN EMOTION REGULATION AND PEER CONFORMITY WITH AGGRESSIVE BEHAVIOR IN SENIOR HIGH SCHOOL STUDENTS - Indriani, Dian; Ghozali Rusyid Affandi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: Aggressive behavior is an ambition to hurt others by expressing negative feelings. This study aims to determine whether there is a relationship between emotion regulation and peer conformity with aggressive behavior among students at SMK Krian 2 Sidoarjo. Method: This research uses a correlational quantitative approach, involving 233 eleventh-grade students as the sample. Then the data analysis was conducted using the JASP version 19.3 for Windows application. Results: Based on the research findings, emotion regulation has been proven to have a quite strong relationship with students' aggressive behavior. Moreover, peer conformity in this study also proved to have a fairly strong relationship with aggressive behavior in students. Novelty: This research applies a phased approach by interviewing guidance counselors. In addition, the initial distribution of the questionnaire was conducted to determine the classes with a high level of aggressive behavior. Unlike previous studies that used random sampling techniques, this research specifically selected classes based on the initial survey results and distributed the main questionnaire using incidental sampling techniques.